YOUTH POLITICAL PARTICIPATION AND ENCOURAGING VOTER REGISTRATION (CIPEEX, 2025)
Youth political participation is essential for a representative and dynamic political landscape.Voter registration strengthens citizenship and ensures that youth demands are considered in decisions that shape the country’s future. The mobilization of this segment contributes to fairer public policies and a political system legitimized by generational diversity. Taking part in the electoral process enables more diverse representation and public policies that meet the needs of young people.This work results from a Master’s dissertation in Sociology at PPGS/UFPB, conducted in 2016, which analyzed the political participation of young people in the Northeast Youth Network between 2005 and 2011. The study sought to understand how these young people perceive political participation, democracy, and citizenship, considering youth as a mutable category, strongly influenced by their own experiences.The results indicate that, although many feel discouraged to participate, there is great potential for engagement when they are adequately encouraged. Initiatives such as dialogue spaces have proven effective in raising awareness about the importance of voting and political involvement. Youth participation strengthens democracy, promotes political renewal, and ensures that their voices are included in the decisions that shape the country’s future.Stimulating this mobilization is essential to making the political system more representative and to addressing the demands of new generations. In this way, youth engagement not only strengthens democracy but also contributes to a fairer and more inclusive system, where the perspectives of this generation are effectively considered in building the future.